Macromolecular Structure Assembly as a Novel Antibiotic Target - Scott Champney (Antibiotics, 2022)
This review discusses the inhibition of macromolecular structure formation as a novel and under-investigated drug target. The disruption of cell wall structures by penicillin-binding protein interactions is one potential target. Inhibition of DNA polymerase III assembly by novel drugs is a second target that should be investigated. RNA polymerase protein structural interactions are a third potential target. Finally, disruption of ribosomal subunit biogenesis represents a fourth important target that can be further investigated. Methods to examine these possibilities are discussed.